Harmonised Regulation as a Catalyst for Cloud Driven Agility in Financial Services Institutions - Meutia, Kardinah Indrianna; Rinaldo (Novatio : Journal of Management Technology and Innovation, 2024)
Cloud adoption in financial services institutions (FSIs) is rising worldwide to improve efficiency, scalability, and innovation. This study investigates how regulatory frameworks, governance maturity, architectural strategies, and organisational culture affect business agility in FSIs using cloud technologies. The research applies a mixed-method design, combining cross-jurisdictional comparisons, case studies, and quantitative metrics. Data were drawn from regulations in the EU, UK, US, and APAC, alongside performance reports from leading FSIs. Indicators included compliance time, deployment frequency, latency improvements, and resilience after cloud migration. The findings show that harmonised regulation reduces compliance burdens, allowing faster technology deployment and innovation. Governance maturity embeds compliance into agile practices, while hybrid and multicloud architectures balance regulatory demands with performance. Proactive compliance checks, regulator engagement, and automation further enhance agility. A strong compliance culture enables responsible innovation. In conclusion, FSIs that combine harmonised regulation, mature governance, flexible architectures, and best practices can sustain agility. Treating compliance as a strategic capability helps institutions innovate, remain resilient, and stay competitive in a fast-changing financial sector